Macro- and microscopic anatomy of the digestive tract in the red-eared slider (Emydidae: Trachemys scripta elegans). - Nonoha Miyai; Takuma Kozono; Tatsu Kuriki; Mai Todoroki; Tomoaki Murakami; Kyosuke Shinohara; Toshinori Yoshida; Tetsuhito Kigata (PLoS ONE)
The red-eared sliders (Emydidae: Trachemys scripta) is characterised by a high adaptability to a variety of environment and threatens the habitat of Japanese native species. The ability to digest a variety of diets may attribute to the high adaptive capacity of this species to various environments, however, the digestive morphology remains scarcely described in red-eared sliders. In this study, we investigated the macro- and microscopic anatomy of the esophagus, stomach, small intestine, and large intestine in red-eared sliders. All segments of the digestive tract had longitudinal mucosal folds, the height and width of which varied in each segment of the digestive tract. The stomach had the highest and widest mucosal folds. The mucosal folds in the proximal-to-middle small intestine exhibited a zigzag shape, whereas those in the distal small intestine were linear. The wall of the digestive tract regularly consisted of mucosa, submucosa, tunica muscularis, and tunica adventitia or serosa. In each segment of the digestive tract, the epithelial structure was different. The esophagus and small intestine were lined by the pseudostratified columnar epithelium. In both segments, the basal part of the pseudostratified epithelium included proliferating cell nuclear antigen (PCNA)-positive proliferating cells. The stomach and large intestine were lined by the simple columnar epithelium. In the stomach and large intestine, PCNA-positive proliferating cells were present in the neck of the proper gastric gland and crypt-like structures, respectively. The proper gastric gland was composed of oxynticopeptic and mucous cells. This study revealed the detailed macro- and microscopic anatomy of the digestive tract in red-eared sliders. Overall, our findings may provide an anatomical basis for understanding the relationship between morphology and function in the digestive tract of turtles.